Representasi Kuntilanak dalam Film Kuntilanak Universe pada Artwear - Darsita, Dede Yogi; Marlianti, Mira; Suharno, Suharno (Mahesa Research Center, 2025)
In general, Kuntilanak is known as the vengeful spirit of a woman who died during pregnancy or childbirth. In Indonesian horror films, Kuntilanak is typically portrayed as a terrifying female ghost seeking revenge after experiencing an unnatural death. However, the Kuntilanak Universe films produced by MVP Pictures offer a different representation. Here, Kuntilanak is depicted as a dual-natured female entity, both frightening and humanized, who can be summoned through the ancient Javanese chant Sekar Durma, titled Lingsir Wengi, and used as a medium for the Mangkujiwo cult's wealth rituals—inspired by the Kuntilanak Universe films, including Kuntilanak (2006), Kuntilanak 3 (2008), Kuntilanak (2018), Kuntilanak 2 (2019), Kuntilanak 3 (2022), Mangkujiwo (2020), and Mangkujiwo 2 (2023), the artist aimed to represent this duality through artwear design. This creative work is significant as no designer has previously explored the Kuntilanak phenomenon from the Kuntilanak Universe films as a concept for artwear. Therefore, the objective of this project is to present a novel form of artwear inspired by these films. The creative process follows four stages: exploration to understand the character and visuals from the films, experimentation with materials and techniques, realization of the designs into an artwear collection, and evaluation to ensure conceptual relevance. The outcome is a series of three artwear looks presented through a fashion cinematic